Data Logger Using PIC - Fazila , Aziz (UTeM, 2009)
A data logger works with sensors to convert physical phenomena into electronic signals such as voltage or current. These electronic signals are then converted or digitized into ADC or DAC data. The data is then easily analyzed by software and stored on a computer hard drive or on other storage media such as memory cards. This project is separated into three parts. The first part includes designing and developing the software for data collection and recording. The program will be collected using windows control software. The output will be analyzed and recorded into table and graph. USB port connection is used to make an interfacing between electronics circuit and computer which is enable the system acquired data from the sensors. The second part of this project is developing the data logger circuit. This circuit used the LCD display as an output that able to display the reading from all sensors. For this part, it is needed to understand about the characteristics of the component used and the connection between electronics to make the circuit well functions. The final part of this project is joining the circuit to the computer using USB port connection to complete the data logger using PIC. Finally it can be monitored through the computer.